Operation optimization of water-cooled central chilling system in a commercial office building based on the gray wolf optimization algorithm - Yang, Jiankun; Zhang, Dongliang; Xu, Aiqin; Guan, Lingjun; Zhou, Wen; Cai, Yang (Frontiers in Built Environment, 2025)
In this study, the gray wolf algorithm was applied to optimize the water-cooled central chilling system operation in a commercial office building. The optimization objective was to maximize the system’s energy efficiency ratio by seeking the optimal number and load distribution of activated chillers, the number and approximate degree of activated cooling towers, and the number and frequency of activated chilled water pumps and activated cooling water pumps. The results show that by using the grey wolf optimization algorithm, the energy efficiency ratio of the refrigeration plant room in the design day increased from 5.03 to 5.51, yielding an increase of 9.67%. The annual comprehensive energy efficiency ratio increased from 5.50 to 6.15, or 11.82%.